THE NEXUS BETWEEN FINANCIAL STABILITY AND ECONOMIC GROWTH IN SOUTHEAST ASIA - Kenedi, Kenedi; Farida, Gina; Hidayatullah, Rizki (JURNAL ILMIAH EDUNOMIKA, 2023)
Financial stability is an important part of economic growth. The main objective in this study is to analyze how financial stability (using Bank Z-Score) affects economic growth. The data used is country-level data from five selected countries in the Southeast Asia region (Indonesia, Cambodia, Malaysia, Philippines, and Thailand) for the period 2011 – 2021 using the ARDL model approach. The results of this study found strong evidence that financial stability (banking stability) has a positive effect on economic growth for countries in the Southeast Asian region. This study also reveals that it is not only financial stability variables that are important to achieve economic growth but investment and trade openness must also be increased if the country want to achieve the expected economic growth. The positive relationship between investment and trade openness implies that investment and trade openness can be beneficial to economic growth. . Keywords : financial stability, economic growth, bank z-score, ARDL